PsycEXTRA Dataset 2014
DOI: 10.1037/e574242014-030
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Dating Violence Victimization and Commitment among Turkish College Women: Does the Investment Model Matter?

Abstract: The present study explored the sexual, physical, psychological, and overall dating violence experiences, and related these experiences to Investment Model variables among Turkish college women. Three hundred and ninety dating women from four universities in Ankara, Turkey completed the Satisfaction, Investment, Alternatives, and Commitment subscales from the Investment Model Scale and the Sexual Coercion, Physical Assault, and Psychological Aggression subscales from the Revised Conflict Tactics Scale. 79.5 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…These results of the research are consistent with the literature (Barreira et al., ; Boladale, Yetunde, Adesanmi, Olutayo, & Olanrewaju, ; Chan et al., ; Fernandez‐Fuertes & Fuertes, ; Ferreira et al., ; Foshee, Reyes et al., ; Lehrer, Lehrer, & Zhao, ; Ohnishi et al., ; Shorey et al., ; Volpe et al., ; Zhang et al., ). Researchers have identified psychological violence as the most common type of bidirectional violence perpetration in dating relationships (Chan, ; Ferreira et al., ; Ohnishi et al., ; Toplu‐Demirtas et al., ; Volpe et al., ; Zhang et al., ). Studies in the United States (Shorey et al., ) and Nigeria (Boladale et al., ) showed that psychological aggression was the most common form of DV (54.9% and 21.9%, respectively), while sexual aggression was the least common (24.3% and 1.6%, respectively) (Boladale et al., ; Shorey et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results of the research are consistent with the literature (Barreira et al., ; Boladale, Yetunde, Adesanmi, Olutayo, & Olanrewaju, ; Chan et al., ; Fernandez‐Fuertes & Fuertes, ; Ferreira et al., ; Foshee, Reyes et al., ; Lehrer, Lehrer, & Zhao, ; Ohnishi et al., ; Shorey et al., ; Volpe et al., ; Zhang et al., ). Researchers have identified psychological violence as the most common type of bidirectional violence perpetration in dating relationships (Chan, ; Ferreira et al., ; Ohnishi et al., ; Toplu‐Demirtas et al., ; Volpe et al., ; Zhang et al., ). Studies in the United States (Shorey et al., ) and Nigeria (Boladale et al., ) showed that psychological aggression was the most common form of DV (54.9% and 21.9%, respectively), while sexual aggression was the least common (24.3% and 1.6%, respectively) (Boladale et al., ; Shorey et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the United States (Shorey et al., ) and Nigeria (Boladale et al., ) showed that psychological aggression was the most common form of DV (54.9% and 21.9%, respectively), while sexual aggression was the least common (24.3% and 1.6%, respectively) (Boladale et al., ; Shorey et al., ). A study in Turkey reported high rates of psychological aggression among women (85.2%) and men (75.6%) in dating relationships (Toplu‐Demirtas et al., ). Our findings highlight the importance of preventing dating violence because psychological violence within dating relationships is regarded as a major determinant of physical violence in future relations (Machado et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are five studies to date with college student samples, and these have mainly focused on sexual aggression in dating relationships. In these studies, prevalence rates of female victimization ranged between 0% and 84% (Aslan et al, 2008;Kabasakal & Girli, 2012;Kayı, Yavuz, & Arıcan, 2000;Toplu-Demirtaş, Hatipoğlu-Sümer, & White, 2013;Yiğitalp, Ertem, & Özkaynak, 2007). Only two studies investigated male sexual victimization (27.9%, Kabasakal & Girli, 2012;0%, Yiğitalp et al, 2007), and only one study (Aslan et al, 2008) measured perpetration of sexual violence in a small female sample, revealing a prevalence of 11.1%.…”
Section: Studies On the Prevalence Of Sexual Aggression In Turkeymentioning
confidence: 99%